The need for ESP in Burundi: What do tertiary English teachers say sbout it? - Nduwimana, Arcade (Journal of NELTA, 2018)
This study examines the views that tertiary English teachers hold on the need for English for Specific Purposes (ESP) in Burundi higher education. To do so, it investigates the extent to which they are familiar with the theory and practice of ESP. For this study, 32 English teachers were contacted to participate in it. They were all requested to complete an online questionnaire, but only 17 proved willing to do so. The findings revealed that the majority of teachers are familiar with the practice of ESP. Although many of them reported to have high familiarity with the field of ESP, a few of them conduct a Needs Analysis (NA) before teaching ESP courses. Results also indicated that tertiary English teachers highly acknowledge the importance of teaching ESP in Burundi higher Education and, therefore, would encourage the ministry of education to fund an ESP project.